161 Use of colchicine in cardiovascular diseases – a systematic review. (6th June 2015) - Mohee, Kevin; Zhang, Jufen; Cleland, John G; Clark, Andrew L
Abstract : Introduction: Colchicine, commonly classified as an anti-inflammatory agent, is a mainstay for the treatment of gout and a second-line therapy for other conditions, including pericarditis, familial Mediterranean fever and Behcet's disease. Recent studies suggest that colchicine may be beneficial in a wide spectrum of cardiovascular diseases. We carried out a systematic review to investigate whether, in randomised controlled trials, colchicine has an effect on the rate of cardiovascular events. Method: Controlled clinical studies were searched in BioMedCentral, the Cochrane Collaboration Database of Randomised Trials (CENTRAL), ClinicalTrials.gov, Google Scholar, MEDLINE/PubMed, Scopus and EMBASE provided they focused on whether colchicine had an effect on primary or secondary prevention of cardiovascular events The PubMed search was performed with the term 'colchicine' and 'randomised'. Results: From 244 citations, eleven randomised controlled trials were identified, of which seven were double-blind. Four trials focussed on the effects of colchicine on coronary atheroma, three on pericarditis, two on atrial fibrillation, one on both pericarditis and atrial fibrillation and one on chronic heart failure. Altogether, 1360 patients were assigned to control and 1323 to colchicine. One substantial trial (n = 523 followed for a median of 3 years) showed that colchicine 0.5 mg/day reduced vascular events (hazard ratio: 0.33; 95% confidence interval [CI] 0.18 to 0.59; p < 0.001). However, a trial of colchicine 0.5 mg/day in 278 patients with chronic heart failure failed to demonstrate an effect on death or heart failure hospitalisation. Meta-analytic pooling showed that colchicine use was associated with a reduced risk of overall cardiovascular events (ACS, in-stent restenosis, postop AF, postop pericardiotomy, postop pericardial effusions, pericarditis and death) with a similar risk of adverse events as placebo. Focussing on the composite of acute vascular occlusion (MI, CVA or CV death), there were 78 events in control groups versus 50 on colchicine. There were 21 deaths in patients assigned to control compared to thirteen assigned to colchicine. Conclusion: Long-term prophylaxis with low-dose colchicine appears safe and may be effective for a number of cardiovascular conditions. Whether colchicine can modify the course of coronary artery disease or heart failure, two cardiovascular conditions associated with activation of inflammatory pathways, deserves further investigation.